CO2 Hydrate Formation Promoted by a Natural Amino Acid l‐Methionine for Possible Application to CO2 Capture and Storage. Issue 8 (12th April 2017) - Cai, Yuanhao; Chen, Yulong; Li, Qijie; Li, Liang; Huang, Haoxin; Wang, Suying; Wang, Weixing
Abstract: We demonstrate thatl ‐methionine, a natural amino acid, can be used to dramatically enhance CO2 uptake kinetics in the formation of CO2 hydrate without the use of energy‐intensive mixing technologies or environmentally harmful chemicals. To the best of our knowledge, l ‐methionine is the most effective promoter to enhance CO2 hydrate formation (at a concentration of 0.2 wt %, the gravimetric capacity reached up to 356 mg g −1 in 1000 min, and t 90 (the time to achieve 90 % of this capacity) was only 15 min). We also present a tentative explanation for the promotion mechanism ofl ‐methionine in the formation of CO2 hydrate from the point of view of structure–property relationship that will help search for more effective promoters. Our results may offer the possibility of practical application of hydrate‐based CO2 capture and storage technology. Abstract : Amino acids sort it out : Hydrate‐based CO2 capture and storage (HCCS) has been considered as a potential approach to mitigate the greenhouse effect. However, it is difficult to realize the industrialization of HCCS technology because of the low formation rate of CO2 hydrate. We show thatl ‐methionine, a natural amino acid, can be used to dramatically enhance CO2 uptake kinetics in the formation of CO2 hydrate with a gravimetric capacity of up to 356 mg g −1 .